Anti-liquefaction performance of partially saturated sand induced by biogas under high intensity vibration. (15th October 2021) - Peng, Erxing; Hou, Zheng; Sheng, Yu; Hu, Xiaoying; Zhang, Dingwen; Song, Li; Chou, Yaling
Abstract: Sand liquefaction is a regular phenomenon caused by events such as earthquakes. As a newly developing treatment, biogas bubbles could mitigate sand liquefaction by decreasing saturation level. This study analyses anti-liquefaction characteristics of sand partially saturated after having been induced by biogas through a shaking table test series. It also analyses the effect of the saturation under high intensity vibration on excess pore water pressure, surface settlement, acceleration amplification coefficient ( β ), and lateral deformation. In addition, the parameter for the characterization, including the saturation ( S r ) and average pore pressure ratio ( r u ‾ ), was used to build an empirical relationship to project the volumetric strain of model subgrade. The results of the study demonstrate that the above indexes can be enhanced by decreasing the saturation and considerably enhancing the liquefaction resistance of sand. In addition, the empirical relationship possesses good volumetric strain prediction efficiency. Therefore, biogas bubbles desaturation used in this study is effective in reducing sand liquefaction. Moreover, Desaturation using biogas bubbles is a novel, effective, pollution-free and environment-friendly liquefaction mitigation method compared to the existing engineering treatment, it is consistent with the purpose of green/sustainable engineering and pollution reduction. Highlights: Novel sustainable, cleaner and bio-based bubbles were used as a liquefaction treatment material. The liquefaction resistance can be improved by introducing biogas bubbles in pore of sand. Excess pore water pressure can be controlled effectively by desaturation method. Deformation and vibration attenuation effect of sand becomes smaller and more obviously by saturation decreasing.